German Minority in the Polish Local Elections = Aktywność mniejszości niemieckiej w polskich wyborach samorządowych - Jarosz, Adam (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The presented paper is an analysis of the German minority participation in the Polish local government elections. The electoral results have been compiled and discussed together with the activity of the German associations at the local governmental level. The German minority is concentrated in the area of the Opole Silesia and is an important political factor in this region.
Keywords: German minority in Poland; local self-government; local elections; mniejszość niemiecka - Polska; władza lokalna; wybory samorządowe